5-(1-Aryl-3-oxo-3-phenylpropyl)-2,2-dimethyl-1,3-dioxane-4,6-diones: synthesis and reactions with N-nucleophiles - Mukhomodyarova, Dinara M.; Ibragimova, Diana K. (Известия Саратовского университета. Новая серия: Серия Химия. Биология. Экология, 2023)
2,2-Dimethyl-1,3-dioxane-4,6-dione (Meldrum acid, isopropylidenmalonate) is widely used by synthetic chemists due to its structural features. The dual nature of the reactivity of Meldrum acid (both electrophilic and/or nucleophilic reagent) determines the synthetic value in the construction of new heterocyclic systems with practically signifi cant properties. A wide range of biological activity has been revealed in a number of compounds containing a 2,2-dimethyl-1,3-dioxane-4,6-dione fragment in their structure. Analysis of periodicals indicates an extremely small volume of literature on the preparation and chemical properties of 5-(1-aryl-3-oxo-3-phenylpropyl)-2,2-dimethyl-1,3-dioxane-4,6- diones, which is a signifi cant omission. It has seemed interesting to obtain 1,5-dicarbonyl compounds based on Meldrum acid as convenient substrates for further nucleophilic transformations into systems with biological activity. For the fi rst time, we have carried out the reaction of 2,2-dimethyl-1,3-dioxane-4,6-dione with 3-aryl-1-phenylprop-2-en-1-ones by stirring in an ethyl alcohol medium in the presence of a catalytic amount of L-proline, which resulted in the corresponding 5-(1-aryl-3-oxo-3-phenylpropyl)-2,2-dimethyl-1,3-dioxane-4,6-diones. The introduction of 5-(1-(4-methoxyphenyl)-3-oxo-3-phenylpropyl)-2,2-dimethyl-1,3-dioxane-4,6-dione in reaction with N-nucleophiles (hydroxylamine hydrochloride, urea, thiourea and semicarbazide hydrochloride) has led to the formation of nucleophilic attack products of the carbonyl group of the acyclic fragment the substrate. The composition and structure of the obtained compounds have been established on the basis of elemental analysis and NMR 1 H, 13C spectroscopy, heteronuclear correlation of HSQC.